Optimising Renal Cancer Patients for Nephron-Sparing Surgery: A Review of Pre-Operative Considerations and Peri-Operative Techniques for Partial Nephrectomy. Issue 1 (February 2017) - Ertemi, Hani; Khetrapal, Pramit; Pavithran, Nevil M.; Mumtaz, Faiz
Partial nephrectomy is the gold standard treatment for T1a renal tumours, with some evidence suggesting that T1b could also be amenable to this approach. However, multiple factors affect the perioperative outcome, including modifiable and nonmodifiable risk factors. Renal function after partial nephrectomy depends on multiple factors, namely pre-operative [baseline kidney function, diabetes, hypertension, high body mass index (BMI), older age and smoking] and intraoperative factors (amount of kidney preserved, ischaemia time). Warm ischemia time should not exceed 25 min, but some evidence suggests that this can be safely extended using cold ischemia. We discuss various pharmaceutical and pre-operative precautions described in the literature to optimise postoperative kidney function, and surgical approaches using open, laparoscopic and robotic techniques. Novel techniques such as selective clamping and zero ischaemia time are promising options with a potential benefit in this area. However, further studies are needed to establish their role in partial nephrectomy. Transperitoneal and retroperitoneal approaches have been used, with the transperitoneal approach being used more commonly. A retroperitoneal approach may have a role in nephron-sparing surgery depending on the location of the tumour. Conclusions: Nonmodifiable factors including pre-operative renal function and amount of healthy renal tissue preserved are the most important predictive factors that determine renal function after partial nephrectomy. Ischaemia time is an important modifiable risk factor and cold ischaemia time should be used if longer ischaemia time is anticipated. New techniques may have a role in maximising postoperative kidney function, but more robust studies are required to understand their potential benefits and risks.